Routledge handbook of contemporary Indonesia - Hefner, Robert W. (Routledge, 2018)
Few countries as culturally rich, politically pivotal, and and naturally beautiful as Indonesia are as often misrepresented in global media and conversation. The Routledge Handbook of Contemporary Indonesia offers an overview of the modern making and contemporary dynamics of culture, society, and politics in this powerful Asian nation. Bringing together original contributions by leading scholars of Indonesia in political science, history, anthropology, sociology, religious studies, and gender studies this handbook provides an up-to-date, interdisciplinary, and academically rigorous exploration of Indonesia.